2016
DOI: 10.1007/s00345-016-1841-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guideline recommendations for management of clinical T1 renal cancers in the Netherlands: a population-based study

Abstract: with PN in cT1a and laparoscopic RN in cT1b were evaluated with logistic regression analyses. Results An increase in nephron-sparing treatment strategies (NSS) of cT1a patients (N total = 2436) was observed; in 2014, 67 % underwent NSS (62 % PN and 5 % thermal ablation). Age, a non-central tumor localization and being treated in a high-volume hospital were associated with PN. Although NSS were applied more frequently over time, the majority (70 %) of cT1b patients (N total = 2205) underwent RN in 2014, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…We found that the proportion of patients with T1a tumours treated by NSS increased by 77% between 2009 and 2013, and that 62% of T1a tumours were treated by this surgical procedure in 2013. With this change, surgical management of T1a tumours in the Australian state of Victoria is now similar to practice patterns found in the Netherlands [15], Sweden [22] and the UK [23].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…We found that the proportion of patients with T1a tumours treated by NSS increased by 77% between 2009 and 2013, and that 62% of T1a tumours were treated by this surgical procedure in 2013. With this change, surgical management of T1a tumours in the Australian state of Victoria is now similar to practice patterns found in the Netherlands [15], Sweden [22] and the UK [23].…”
Section: Discussionmentioning
confidence: 62%
“…While others have suggested that greater use of laparoscopic surgical procedures may be hindering the uptake of NSS for T1b tumours , our results suggest that this may not be the case in Australia. Our rates of NSS for T1b tumours in 2013 were similar to levels found in the USA in 2009 (18%), but lower than levels seen in the Netherlands (28%) in 2013 . The present study suggests that, in Australia, T1b tumours are still largely treated by radical nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for surgery strictly follow the European Association of Urology (EAU) guidelines for treatment of renal tumors [2]. Resection is preferred before nephrectomy in all T1 category (≤7 cm) cases [9, 10, 11]. In resection, as well as in nephrectomy, preference is given to the less invasive approach (laparoscopic, even robotically assisted) before open surgery [12].…”
Section: Introductionmentioning
confidence: 99%
“…Aben et al [1] have focused on adherence to guideline recommendation for management of clinical T1 renal cancers in the Netherlands. In this populationbased study, the implications of national and international guidelines are well evaluated and provide insight on how adherence to guidelines could be compared across different health care systems in Europe.…”
mentioning
confidence: 99%